(untitled) (Eurasian Scientific Herald, 2022)
The study studied the linguistic features of anthroponyms as units of language and units of intercultural communication. The article considers a look at the history of the emergence and development of English anthroponyms, the definition of their types and properties, and determines the methods of transferring anthroponyms within the framework of intercultural and interlingual communication